An investigation of the optimum separation conditions in the Degassing stations of one of southern Iraqi oil Field - AL-Maliki, Madhi A. R. Swadi (Journal of Petroleum Research and Studies, 2019)
In field separation facilities operation, operators tend to determine the optimum conditions to maximize revenue. The object of this study is to investigate the present number of separation stages and their optimal conditions for degassing stations of oil Field. A computer program model was written to predict the optimal conditions for oil field gas-oil separation stations subject to a given crude oil composition , flow rate and feed temperature and pressure using flash calculations with modified Soave-Redlich-Kwong Equation of state. Nine Bottom-hole well samples of reservoir crude oil was collected and subjected to PVT analysis commonly performed on crude oil, Surface stage separators gas samples at steady condition were taken and analyzed by gas chromatography apparatus to determine the gas composition. A good agreement was found by comparing theoretical and experimental prediction for gas composition. The results indicate that the present five separation stages is the optimum number and the values obtained for these optimum stages pressure are (514.7,119.7,42.7,26.7,14.7 psig) for Summer and (464.7,119.7,42.7,26.7,14.7 Psig) for Winter where the current operation pressures are (614.7,119.7,42.7,26.7,14.7 psi) for Summer and Winter. The total liquid yields in stock tank reaches (1.29, 1.31 %) for summer and winter respectively and the stock tank API Gravity reaches (0.41, 0.42) for summer and winter respectively.